Hidrosefalus dan Tatalaksana Bedah Sarafnya - Khrisna Rangga Permana (PT. Kalbe Farma Tbk., 2018)
Hidrosefalus merupakan kondisi penumpukan carian serebrospinal (CSS) mengakibatkan peningkatan tekanan intrakranial (TIK) dan juga penekanan jaringan normal sekitar. Hidrosefalus dapat akibat gangguan produksi, aliran atau penyerapan CSS. Prevalensi hidrosefalus sekitar 3 tiap 1000 kelahiran. Penanganan dengan shunt atau pengaliran ke tempat lain melalui teknik ETV (endoscopic third ventriculostomy).Hydrocephalus is a condition when cerebrospinal fluid (CSF) build-up results in increased intracranial pressure (ICP) and suppression to normal surrounding tissue. Hydrocephalus may occur due to interference with the production, flow or absorption of CSF. The prevalence is about 3 per 1000 births. CSS excess is managed by shunt or drainage through ETV (endoscopic third ventriculostomy).